A participação esplênica e vagal na deposição de lipídeos no tecido adiposo marrom de ratos obesos e não obesos - Nottar, Cassiane Lisbinski (2022)
Brown Adipose Tissue (BAT) is specialized in thermogenesis, a process that involves the degradation of energetic substrates, especially lipids, and the formation of a mitochondrial electrochemical gradient that is dissipated by the mitochondrial uncoupling protein (UCP-1) in the form of heat. Classically, thermogenesis is stimulated by the activity of the Sympathetic Nervous System (SNS), which is reduced in obesity. Studies indicate that the parasympathetic branch, via the Vagus Nerve (NV) is able to influence thermogenesis in BAT. Obese people have vagal hyperactivity. NV also modulates the immune response, and its anti-inflammatory effects depend on the presence of the spleen. In the present study, the histological parameters of BAT in obese and non-obese rodents undergoing vagotomy associated with splenectomy were evaluated. For this, obesity was induced by the subcutaneous injection of monosodium glutamate (M; 4g/Kg) in the first postnatal week. Control (CTL) or nonobese rats received equimolar saline. M and CTL were weaned at 21 days, and at 60 days of life they were randomly assigned to groups according to surgery: Splenectomy (spl) – removal of the spleen; vagotomy (vag) – NV section; spl+vag (both surgeries) and false-operated (sham) – surgical stress simulation (n=6 rats/group). At 150 days of age and after 12 hours of fasting, the animals were weighed and euthanized, and the BAT of the interscapular region was removed, cleaned, washed and weighed. Part of the TAM was transferred to a fixative and submitted to histological technique and staining with hematoxylin and eosin (HE). Data were expressed as mean±SEM, using the Student's t test or two-way ANOVA with Tukey's posttest (p<0.05). M rats are smaller, with a higher BAT weight, in which there is a higher lipid content compared to CTL animals (p<0.05). In the CTL group, vag reduces body weight, BAT weight and fat deposition n in relation to sham. Spl reduces the number of nuclei and increase fat deposition in the BAT of CTL animals. On the other hand, in M-obese patients, vag does not significantly alter any parameter of the SAT, while spl increases the number of nuclei. Thus, the present study indicates that NV modulates the lipid content in the BAT of non-obese rats, without splenic interference. In obese subjects, however, the effect of NV seems to be absent, while the spleen, through an unknown route, influences the BAT of obese rats.